The social determinants of healthy ageing in the Canadian Arctic. Issue 1 (1st January 2019) - Baron, Marie; Riva, Mylène; Fletcher, Christopher
ABSTRACT: A better knowledge of the social determinants of health (SDH) promoting healthy ageing in Inuit communities is needed to adapt health and social policies and programs. This study aims to identify SDH associated with healthy ageing. Using the 2006 Aboriginal Peoples Survey (n = 850 Inuit aged ≥50 years), we created a holistic indicator including multiple dimensions of health and identified three groups of participants: those in 1) good 2) intermediate and 3) poor health. Sex and age-adjusted multinomial regression models were applied to assess the associations between this indicator and SDH measured at the individual, household and community scales. In comparison to APS respondents in the "Poor health" profile, those in the "Good health" profile were more likely to have a higher individual income, to participate in social activities, and to have stronger family ties in the community ; those in the "Intermediate health" profile were less likely be in a relationship, more likely to live in better housing conditions, and in better-off communities. Results indicate that SDH associated with the "Good health" profile related more to social relationships and participation, those associated with the "Intermediate health" profile related more to economic and material conditions.